Assessing the Diversity of Marine Bacterial β-Glucosidases by Capillary Electrophoresis Zymography - Arrieta, Jesús M. (American Society for Microbiology, 2001)
We propose a new method for the fast separation and detection of β-glucosidases in environmental samples. With this approach, β-glucosidases extracted from bacteria are evidenced by substrate-incorporated capillary electrophoresis (CE zymography) and their kinetic parameters can be determined by repeated injections using different substrate concentrations. Preliminary results obtained with natural bacterial communities from the coastal North Sea suggest that the diversity of β-glucosidases in the marine environment might be much higher than previously observed.